2021
DOI: 10.1021/acs.jcim.1c00104
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Oxidation: Role of Membrane Phase-Separated Domains

Abstract: Lipid oxidation is associated with several inflammatory and neurodegenerative diseases, but many questions to unravel its effects on biomembranes are still open due to the complexity of the topic. For instance, recent studies indicated that phase-separated domains can have a significant effect on membrane function. It is reported that domain interfaces are “hot spots” for pore formation, but the underlying mechanisms and the effect of oxidation-induced phase separation on membranes remain elusive. Thus, to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 73 publications
0
7
1
Order By: Relevance
“…4a and 4f), indicating an increase in the membrane order. This stands in contrast to our assumption that lipid peroxidation would shorten the fluorescence lifetime, given that a geometrically disordered bilayer causes an increase in water permeability, and thus, an increase in membrane polarity [34][35][36][37] . To deeply understand how the mitochondria were damaged, the light-induced lipid oxidation process was then recorded using FLIM in time-lapse mode.…”
Section: Evaluation Of the Mitochondrial Staining Ability The Promine...contrasting
confidence: 86%
“…4a and 4f), indicating an increase in the membrane order. This stands in contrast to our assumption that lipid peroxidation would shorten the fluorescence lifetime, given that a geometrically disordered bilayer causes an increase in water permeability, and thus, an increase in membrane polarity [34][35][36][37] . To deeply understand how the mitochondria were damaged, the light-induced lipid oxidation process was then recorded using FLIM in time-lapse mode.…”
Section: Evaluation Of the Mitochondrial Staining Ability The Promine...contrasting
confidence: 86%
“…Lipid peroxidation is a cascading event initiated by ROS attacking anionic headgroups at membrane interfaces [ 804 ] where oxidized moieties residing close to lipid headgroups perturb membrane bilayer structures, modifying membrane properties including increasing membrane permeability [ 805 ], decreasing membrane fluidity [ 806 , 807 ], and increasing line tension, which can transform nanometer-scale lipid rafts into larger, micron-sized domains [ 776 , 808 , 809 ] that carry pro-inflammatory molecules often associated with cancer cell signaling pathways [ 328 , 777 , 780 ]. Experimental results using giant membrane vesicle model systems showed that lipid peroxidation induced significant changes in membrane phase behavior, causing a dramatic escalation of phase separation at room temperature, which increased the non-raft phase while decreasing affinity of tested raft proteins for raft domains [ 810 ].…”
Section: The Effects Of Melatonin On Lipid Phase Transition Lipid Com...mentioning
confidence: 99%
“…27−29 Such changes in the membrane may lead to an increase in permeability for polar molecules like water. 27,30,31 Increased plasma membrane permeability can make a cell more susceptible to spontaneous pore formation, leading to solute imbalance and cell death. 7,32 While there has been significant study on how phospholipid oxidation can alter the material properties of the lipid bilayer, little is known about how changes in these properties are connected to the behavior of integral membrane proteins.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For instance, one possible result of a free-radical chain reaction in the lipid bilayer is the scission of a fragment of a phospholipid tail, resulting in the altered lipid molecular area and potential removal of the cleaved tail from the bilayer . Lipid oxidation causes a decrease in membrane thickness and a drastic change in area per lipid depending on the degree of oxidation. , Changes to lipid conformation are due to the tendency of the cleaved tail to be in the proximity of the headgroup region, forming hydrogen bonds with water molecules. Such changes in the membrane may lead to an increase in permeability for polar molecules like water. ,, Increased plasma membrane permeability can make a cell more susceptible to spontaneous pore formation, leading to solute imbalance and cell death. , …”
Section: Introductionmentioning
confidence: 99%